Effect of mooring line configurations on the dynamic responses of truss spar platforms - Montasir, O.A. (Elsevier Ltd, 2015)
Considering the cost impact of mooring lines on the overall project, it is essential to find the best possible mooring configuration for a given platform and metocean data, which reduces the motion responses of the platform to an acceptable level. In this paper, the effect of symmetric and asymmetric mooring configurations in terms of line azimuth angles on the platform responses is studied. A truss spar platform is modelled as a rigid body with three degrees-of-freedom and the dynamic response analysis of the platform is performed in time-domain by computing the wave kinematics and water wave force using linear Airy wave theory and modified Morison equation, respectively. The responses of the platform are found to be not significantly affected by changing mooring line configurations in terms of azimuth angles. However, the initial offset of the platform is significantly affected with mooring line configurations. Â©2015 Elsevier Ltd. All rights reserved.